Effectiveness Of Video-Based Progressive Muscle Relaxation On Pain Intensity And Sleep Quality Among Patients With Osteoarthritis - Putra Ardhana; Eben Haezar Kristian; Elisabeth Wahyu Savitri; Marsela Oktavia Yunita (Griya Eka Sejahtera, 2026)
Background: Osteoarthritis is a degenerative joint disease commonly associated with chronic pain and sleep disturbances, which significantly reduce patients’ quality of life. Persistent pain and poor sleep quality often interact bidirectionally, leading to worsening physical and psychological conditions. Therefore, effective, feasible, and non-pharmacological interventions are needed to manage pain and improve sleep quality. This study aimed to evaluate the effectiveness of video-based progressive muscle relaxation on pain intensity and sleep quality among patients with osteoarthritis. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted in healthcare facilities in Pontianak, Indonesia. A total of 50 patients with osteoarthritis were recruited using purposive sampling and assigned to an intervention group (n = 25) and a control group (n = 25). The intervention group performed video-based progressive muscle relaxation once daily for seven consecutive days in addition to standard care, while the control group received standard care only. Pain intensity was measured using the Numeric Rating Scale (NRS), and sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Mann–Whitney U test. Results: The intervention group showed significantly greater reductions in pain intensity and improvements in sleep quality compared with the control group (p < 0.001). The magnitude of change in both outcomes was substantially higher in the intervention group, indicating a strong effect of video-based progressive muscle relaxation. Conclusion: Video-based progressive muscle relaxation is effective in reducing pain intensity and improving sleep quality among patients with osteoarthritis. This intervention has important implications for nursing practice and health sciences, as it provides a practical, safe, and easily implemented non-pharmacological strategy to support self-care management in patients with chronic musculoskeletal conditions